Diagnóstico de la situación de la participación política de los jóvenes en relación con el municipio de Quito, en el barrio Carapungo - Quito, desde el 2011 - Cevallos Trujillo, Byron David (2015)
To think about youth and their relationship among State, hegemonic culture and political participation implies a theoretical-practical analysis from the experiences of youth processes in Ecuador against the traditional political sphere. This document approaches the reality of two youth organizations in Quito, "Red Cultural Calderón" and "Organización Sarta Indígena", in order to analyze their policies and practices in their everyday life; to understand how they relate to the institutions, like the Municipality of Quito; and, finally, to know their proposals to build a participatory and democratic citizenship, in which young people be the protagonists from its cultural and political diversity.